Coronary ostial aneurysms following aortic root replacement in patients with familial aortic aneurysm are common and support the need for long-term surveillance. (December 2019) - Krishna, Hema; Ginde, Salil; Katzmark, Lindsey; Mitchell, Michael; Woods, Ronald; Hraska, Victor; Earing, Michael G.
Abstract: Background: Following the successful aortic root replacement (ARR) in patients with familial forms of aortic aneurysms (FFAA), few studies have defined the long-term outcomes of the re-implanted coronary arteries. The goal of the study was to describe late coronary complications following ARR in patients with FFAA. Methods: 40 patients with a genetically confirmed form of FFAA S/P ARR whom had undergone at least 1 CT scan or cardiac MRI study following ARR were identified. All studies were reviewed retrospectively and the coronary ostium were measured offline by two independent observers. Results: The majority of patients had Marfan Syndrome (80%), 15% had Loeys-Dietz Syndrome (TGFBR1 or TGFBR2), and 2 patients a MYLK or ACTA2 mutation. Mean age at time of ARR was 30.7 years, range 10–65. Mean length of follow-up from ARR 6.2 years, range 0.5–19. At last follow-up, 55% had developed at least 1 coronary complication. Nineteen (48%) had developed a coronary ostium aneurysm and 3 patients coronary ostium stenosis. All patients were alive at last follow-up. No patient had developed a coronary button rupture or dissection. Patients with aneurysms were more likely to have a mutation other than Marfan Syndrome (p < .05) and were more likely to have undergone emergent ARR following dissection (p = .008). Progressive coronary ostium dilation was rare. Two patients however did develop severe dilation and required button revision, both with TGFBR2 mutation. Conclusion: Coronary ostium dilation is common following ARR in patients with FFAA. Progressive dilation and risk for coronary button rupture appears to be low. Patients with non-fibrillin 1 mutations, are at higher risk for severe dilation and some may require intervention. Long term surveillance in particular in patients with non-fibrillin1 forms of familial aortic aneurysm and dissection syndrome should be considered. Highlights: Coronary ostium dilation is common following aortic root replacement in patients with familial aortic aneurysms. Progressive dilation and risk for coronary button rupture appears low. Patients with non-fibrillin 1 mutations, are at higher risk for severe dilation and some may require intervention. Following aortic root replacement in patients with non-fibrillin forms of familial aortic aneurysms long term surveillance should be considered.